THE INFLUENCE OF GREEN INTELLECTUAL CAPITAL DISCLOSURE ON ENVIRONMENTAL PERFORMANCE AND FIRM VALUE IN INDONESIA - servatia mayang setyowati; Franciscus Ardhito Bagaskara ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2026)
This study examines the effect of green intellectual capital disclosure on firm value, both directly and indirectly through environmental performance as a mediating variable. The research is motivated by growing concerns about sustainability and the persistence of information asymmetry in capital markets, which encourages investors to demand more transparent and credible corporate information. In addition, companies are increasingly pressured to obtain legitimacy through sustainability practices that align with stakeholder expectations. This research employs a quantitative research design, using purposively selected firms listed on the Indonesian capital market. The relationships among variables are analyzed using Ordinary Least Squares regression. The findings indicate that green intellectual capital disclosure functions as a strategic signal that reduces investor uncertainty and enhances market confidence, thereby increasing firm value. Broader sustainability disclosure practices encourage companies to improve their environmental achievements, indicating the realization of corporate sustainability commitments while simultaneously enhancing external legitimacy. Environmental performance further functions as an intermediary pathway through which green intellectual capital disclosure influences market valuation. These findings imply that firm value is shaped not only by the communication of sustainability information but also by the company’s tangible environmental practices and achievements. Therefore, integrating transparency and sustainability practices is important for enhancing corporate credibility and investor trust.